Parental Encouragement to Their High School Children to Learn English in a Socio-Educative Context - Softa, Valbona Loshi (European Journal of Multidisciplinary Studies, 2022)
Due to an increasing highlight of English language learning in formal education in Albania, this research addresses the importance of parental support and encouragement to their high school children. It aims to measure the intensity of parental encouragement with a standard instrument (AMTB, Gardner R.C., 2004), scored by a Likert scale at the range (1-6) on a sample (N=470) high school students, falling into three main groups of schools: public urban high schools, public rural high schools and non public high schools. The data gathered was processed with (SPSS 18) and the analysis conducted in the research include the descriptive statistics to find the mean values and the frequencies for the overall parental encouragement in the total sample and a one-way Anova procedure and Post Hoc Tykey HSD was conducted to find the variances of parental encouragement impacted by the three groups of schools. The results indicated that that the mean value for the overall parental encouragement to learn English language M = 4.13, DS=.7. 53.2 percent of the respondents state they are not encouraged by their parents to learn English language, whereas, 46.8 percent students state they are encouraged by their parents. There existed very slight differences between groups: for urban public high school and rural high school the difference was (.13473), and statistically insignificant at value (p=.020). Urban public schools compared to non-public schools the difference is (-.08733), statistically not significant (p = .459), as the value (p) in the comparisons for these groups is (greater than .05). For the group of students in non-public schools and students of rural public schools the difference is (.22206) and the result is statistically significant, (p = .005).
Keywords: parental encouragement, learn English, socio-educative context, urban and rural high schools, educational context, public/non public high schools